An Adaptation Strategy Lasmi in Maintaning Its Existence As Waranggana Tayub in Grobogan Regency - Widihastuti, Santi; Sunarto, Sunarto; Udi Utomo, Udi Utomo (Universitas Negeri Semarang, 2019)
Various attempts were made by an artist to maintain its existence, Lasmi waranggana tayub is an artist who did the adaptation strategy to maintain its existence in Grobogan. This study aimed to analyze the adaptation strategies that do Lasmi to maintain its existence as a waranggana tayub dikabupaten Grobogan. This research method is qualitative. The data collection techniques is using observation, interviews, document study. Mechanical validity of the data is using triangulation of data and resources, while the data analysis procedures with data reduction, data presentation, and draw conclusions. The results of the study, Lasmi started his career at age 11 years and able to maintain its existence until now at the age of 60 years. Existence Lasmi shown with active Lasmi in any activity tayub Arts in Grobogan. The efforts are being made by Lasmi that still exist to do the process of learning and cultural modification. The learning process is carried out Lasmi based on their awareness to improve themselves, to always keep abreast of the times. The learning process is carried out Lasmi classified into two types, namely singing or vocal learning, and the learning process of recording. While modifications were made Lasmi culture is, by displaying a new presentation form Tayub Art performances, namely in the form of tapes. Lasmi is a waranggana tayub first recording, so that through Lasmi Music tayub in Grobogan developed rapidly and became more famous Lasmi name everywhere. The implications of this research for art education, especially formal art education as a source of locally-based arts learning. Suggestions for artists tayub, particularly in Grobogan in order to keep up with changing times, to continue to improve themselves through adaptability, as well as constantly improving the quality of the vocals.